Analisis Green Accounting Sebagai Implementasi Sustainable Development pada Industri Kimia di Karawang: Studi Kasus PT. Timuraya Tunggal - Rd. Vera Gartika Kusumah; Lilis Lasmini; Hendri Nur Ardiansyah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the implementation of green accounting in the context of sustainable development at PT Timuraya Tunggal Karawang, which serves to provide environmental information to stakeholders. The method applied is descriptive qualitative using observation, interview, and literature study techniques. Data analysis was conducted using the Miles & Huberman model which includes data reduction, data presentation, and conclusion drawing. The research findings show that the company has allocated costs for environmental activities, but it has not been specifically recorded in the financial statements. The implementation of sustainable development is carried out through the Triple Bottom Line (TBL) approach, including the implementation of Corporate Social Responsibility (CSR) programs in Anggadita Village. In addition, the company also participated in the PROPER program and achieved a Blue rating, indicating compliance with environmental management standards.